Discrimination of Human Urine from Animal Urine Using 1H-NMR. Issue 1 (28th August 2018) - Lee, Wonho; Ko, Beom Jun; Sim, Yeong eun; Suh, Sungill; Yoon, Dahye; Kim, Suhkmann
Abstract: Urine was most commonly used biological sample in drug test. To create a false-negative test result, some drug abusers were reported to submit animal urine instead of their own. So, the purpose of this study was to compare and differentiate human from animal urine (Rat 370, Pig 12, Horse 10, Cat 8, Dog 13, Cow 10, Monkey 10) samples through the uses of quantitative 1 H-NMR and to find biomarkers that can be used for the discrimination of human urine from animal urine. The 1 H-NMR spectroscopy was employed and metabolomic analysis with multivariate statistics was carried out. Human urine samples and animal urine samples showed different patterns in metabolites profile and several characteristic metabolites were identified.